STRATEGI PENYAMPAIAN INFORMASI DALAM FILM MONSTER KARYA RAKO PRIJANTO TANPA MENGGUNAKAN DIALOG - Pratama, M. Akhdan; Wahyu Nova Riski (Ilmu Komunikasi, FISIP Universitas Pasundan, 2025)
Non-dialogue films are increasingly rare in the modern era, where advanced sound recording and editing technologies dominate film production. Non-dialogue films must employ specific strategies to convey information effectively to the audience. This study aims to identify the strategies used in the film Monster (2023) to communicate information without relying on dialogue. The research method employed is qualitative, with the object of study being Monster (2023), directed by Rako Prijanto. Data were collected from audiovisual materials, documentation, and interviews. The theories applied in the analysis include David Bordwell’s theories of mise-en-scene and narrative, as well as dialogue theories from Armantono & Suryana and Sarah Kozloff. The findings indicate that mise-en-scene is the primary strategy used to replace the function of dialogue in conveying information. Among the elements of mise-en-scene, staging: movement and performance emerges as the most dominant, appearing in 29 out of 57 scenes. This is followed by setting, present in 15 scenes; lighting, highlighted in 8 scenes; costume, featured in 5 scenes; and makeup, which has no significant impact on information delivery. These mise-en-scene elements convey varying intensities of information such as emotion, setting, character identity, and atmosphere. Therefore, the use of mise-en-scene in this film proves to be an effective strategy for substituting dialogue in the communication of information. These findings have direct implications for the film industry, suggesting that filmmakers can effectively utilize mise-en-scene elements to create engaging non-dialogue films.